High signal intensity in dentate nucleus and globus pallidus on unenhanced T1‐weighted MR images in three patients with impaired renal function and vascular calcification. (11th January 2016) - Barbieri, Sebastiano; Schroeder, Christophe; Froehlich, Johannes M.; Pasch, Andreas; Thoeny, Harriet C.
Abstract : Gadolinium‐based contrast agents (primarily those with linear chelates) are associated with a dose‐dependent signal hyperintensity in the dentate nucleus and the globus pallidus on unenhanced T1‐weighted MRI following administration to selected patients with normal renal function. The accumulation of gadolinium has also been reported in the skin, heart, liver, lung, and kidney of patients with impaired renal function suffering from nephrogenic systemic fibrosis (NSF). Here we report on three patients with impaired renal function and vascular calcification (two with confirmed NSF) whose unenhanced T1‐weighted MRIs showed conspicuous high signal intensity in the dentate nucleus and the globus pallidus after they had been exposed to relatively low doses of linear gadolinium‐based contrast agents (0.27, 0.45, and 0.68 mmol/kg). Signal ratios between dentate nucleus and pons and between globus pallidus and thalamus were comparable with previously reported measurements in subjects without renal impairment. Of note, all three analysed patients suffered from transient signs of neurological disorders of undetermined cause. In conclusion, the exposure to 0.27‐0.68 mmol/kg of linear gadolinium‐based contrast agent was associated with probable gadolinium accumulation in the brain of three patients suffering from impaired renal function and vascular calcification. © 2016 The Authors. Contrast Media & Molecular Imaging published by John Wiley & Sons Ltd. Abstract : We report on three patients with impaired renal function and vascular calcification (two with confirmed nephrogenic systemic fibrosis) whose unenhanced T1‐weighted MRIs showed conspicuous high signal intensity in the dentate nucleus and the globus pallidus after they had been exposed to relatively low doses of linear gadolinium‐based contrast agents (0.27, 0.45, and 0.68 mmol/kg). Of note, all three analysed patients suffered from transient signs of neurological disorders of undetermined cause.